Development of Arabic Vocabulary Gamification Model Using The Fuzzy Delphi Method - Jaffar, Mohammad Najib; Zainuddin, Nurkhamimi; Muhammad Nawawi, Mohd Adi Amzar; Rahman, Azman Ab; Ahmad, Mohammad Imran; Mohd. Yazid, Mohd. Taqwudin; Syawie, Faizal Ridhwan (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aims to obtain the consensus of experts on the needs of the main element and sequence position (ranking) priority for each item in the design development of the model gamification vocabulary in Arabic. This study employed the fuzzy Delphi approach using a seven-point Likert scale. This work aimed to create a model gamification vocabulary for Arabic based on expert consensus. Consequently, the researchers gathered the opinions of nine experts from various sectors, particularly Arabic language, technology education, and Arabic language industry participants. This 21-item survey questionnaire has three primary components: (i) informational elements, (ii) interface elements, and (iii) the element of interactivity. Triangular fuzzy numbering was used to analyze the data. A defuzzification process establishes each item's position (ranking). The results demonstrate that experts agree on every point in the primary element. The results demonstrate that experts agree on every point in the primary element. The results indicate that every item received met or exceeded the three fuzzy criteria: the threshold value (d) does not exceed or equal 0.2, the percentage of deal experts exceeds or equals 75%, and the defuzzification (alpha cut) value exceeds or equals 0.5. The Arabic Gamification Vocabulary Model should provide the educational sector with fresh ideas that align with the nation's digital education policy.